Laryngeal myofascial pain syndrome as a new diagnostic entity of dysphonia. Issue 2 (April 2017) - Jung, Soo Yeon; Park, Hae Sang; Bae, Hasuk; Yoo, Jeong Hyun; Park, Hyung Jun; Park, Kee Duk; Kim, Han Su; Chung, Sung Min
Abstract: Objective: To consider the feasibility of diagnosing intrinsic laryngeal muscle myofascial pain syndrome (MPS) in dysphonic patients who demonstrated immediate symptom and stroboscopic finding improvement after laryngeal electromyography (LEMG) without further treatment. Methods: A chart review of patients who showed subtle vocal fold movement abnormalities on a stroboscopic examination and underwent ultrasonography (US)-guided LEMG was performed. Patients with vocal fold paralysis, mucosal lesions, spasmodic dysphonia, and vocal tremor on stroboscopic examination were excluded. Among them, patients with normal EMG findings were included in this study. The patients who reported voice symptom improvement after LEMG without further treatment were placed in laryngeal MPS (LMPS) group and the other patients were placed in non-laryngeal MPS (non-MPS) group. Predisposing factors, voice symptom, symptom-duration, and stroboscopic findings of these patients were reviewed. Results: Among the 16 patients, LEMG findings were normal, five (31%) were included in the LMPS group and the other 11 patients (69%) were included in the non-MPS group. All LMPS group patients had a history of voice abuse and reported odynophonia. The Korean Voice Handicap Index-10 score decreased significantly after US-guided LEMG without additional treatment in the LMPS group. The stroboscopic findings revealed that vocal fold hypomobility was the most common finding in the LMPS group, and two patients showed a muscle tension dysphonia pattern. The LMPS groups showed improvement of vocal fold mobility on 1-week stroboscopic evaluation. Conclusion: LMPS is a potential diagnosis for patients with vocal fold hypomobility finding on stroboscopic findings but with normal EMG results. Diagnosis of LMPS could be considered in patients who showed symptom and vocal fold movement improvement after LEMG.